PINTU TERBUKA, ARENA TERTUTUP: REPRODUKSI KETIDAKSETARAAN SIMBOLIK PADA MAHASISWA PENERIMA KIP-K DALAM KERANGKA SOSIOLOGI BOURDIEU - Tasya Lutfiah; Satriyo Wibowo; Riko Septiantoko (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The KIP-K (Smart Indonesia Card for Higher Education) program is designed to expand access to higher education for low-income groups. However, financial access does not automatically generate equality in the social and symbolic experiences of scholarship recipients. This study aims to analyse how KIP-K, despite being designed as an equalisation instrument, is structurally implicated in the reproduction of symbolic inequality. The method employed is a systematic critical review of 29 purposively selected sources from 2006–2026, encompassing Pierre Bourdieu's theoretical works, empirical studies of KIP-K students' experiences, and policy evaluations. Analysis draws on Bourdieu's conceptual framework, habitus, capital, field, and symbolic violence as a reading lens for literature findings. Results identify six simultaneously operating mechanisms of symbolic inequality reproduction: (1) habitus cleft, (2) consumptive distinction, (3) institutional symbolic violence, (4) cultural capital gap, (5) policy stigma, and (6) spatial implementation disparity. These six mechanisms produce a condition termed Pseudo-Inclusion where formal inclusion occurs, but symbolic inequality is latently reproduced. Findings imply the need to reorient scholarship policy design beyond financial intervention toward transforming the structural conditions of the higher education field.